Prokineticin-2 prevents neuronal cell deaths in a model of traumatic brain injury - Zhongyuan Bao (Nature Portfolio, 2021)
Prokineticin-2 (Prok2) is a secreted protein involved in many physiological processes. Here, the authors show that Prok2 prevents neuronal cell ferroptosis after traumatic brain injury and its administration before cortical injury reduces neuronal degeneration, and motor and cognitive impairments.